Morphometric traits and identification of GH and IGF-1 gene polymorphisms in Napu buffalo (Bubalus bubalis) from Central Sulawesi, Indonesia. (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: The objectives of this study are to measure the body weight (BW) and morphometric parameters of Napu buffaloes, identify the growth hormone (GH) and insulin-like growth factor-1 (IGF-1) gene polymorphisms, and associate them with the BW and morphometric parameters of Napu buffaloes. Materials and Methods: This study used 39 Napu buffaloes (9 males and 30 females). Morphometric measurements were performed using a measuring tape. The GH and IGF-1 gene diversity analysis was performed using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) and direct sequencing techniques. Results: The results showed that there is diversity in BW and body size of Napu buffaloes due to the influence of age and sex. The results of PCR-RFLP analysis of the GH|AluI gene showed 0% VV, 100% LL, and 0% VL genotypes. While the IGF-1|SnaBI gene shows the genotype AA 0%, BB 100%, and AB 0%. The sequencing results of the GH and IGF-1 genes in Napu buffaloes did not find mutations. Conclusion: Age and sex in Napu buffaloes may affect BW and body size. The GH and IGF-1 genes in Napu buffaloes are monomorphic, so no association can be made with the morphometric parameters of Napu buffaloes.J. Adv. Vet. Anim. Res., 12(1): 205–213, March 2025http://doi.org/10.5455/javar.2025.l887